A study on data analysis utilizing the K-edge absorption spectroscopy in mixed thorium and uranium solutions - Han Yang; Li Li; Quanwei Liu; Yingjie Ma; Jianbin Zhou; Liudong Hou; Yongquan Qin; Yantao Hu; Jing Ma (International Journal of Advanced Nuclear Reactor Design and Technology)
X-ray absorption spectroscopy stands as a non-destructive assay technique commonly employed in nuclear fuel reprocessing plants to analyze the concentration of elements such as uranium, plutonium,thorium.The processing of absorption spectroscopy directly affects the measurement outcomes. In this study, an experimental setup for K-edge absorption spectrum has been established. Acknowledging the constraints of conventional K-edge absorption spectrum analysis, two improved methods are proposed, including the optimized method, and the cumulative counting method. A mixed sample of thorium and uranium was utilized to conduct an experimental study. Upon analyzing and experimental results, it was determined that the cumulative counting method offers better accuracy and simplicity in processing the absorption spectrum. During the spectrum processing, adopting a wide region of interest enhances the precision of results and reduce relative deviations, while omitting background subtraction aids in simplifying the process. The cumulative counting method can also be extended to the L-edge absorption spectrum.